Predominance of G9P[8] rotavirus strains throughout France, 2014–2017. (June 2018) - Kaplon, J.; Grangier, N.; Pillet, S.; Minoui-Tran, A.; Vabret, A.; Wilhelm, N.; Prieur, N.; Lazrek, M.; Alain, S.; Mekki, Y.; Foulongne, V.; Guinard, J.; et al.
Abstract: Objectives: Group A rotavirus is a major cause of acute gastroenteritis in young children worldwide. A prospective surveillance network has been set up in France to investigate rotavirus infections and to detect the emergence of potentially epidemic strains. Methods: From 2014 to 2017, rotavirus-positive stool samples were collected from 2394 children under 5 years old attending the paediatric emergency units of 13 large hospitals. Rotaviruses were genotyped by RT-PCR with regard to their outer capsid proteins VP4 and VP7. Results: Genotyping of 2421 rotaviruses showed that after a marked increase in G9P[8] (32.1%) during the 2014–2015 season, G9P[8] became the predominant genotype during the 2015–2016 and 2016–2017 seasons with detection rates of 64.1% and 77.3%, respectively, whereas G1P[8] were detected at low rates of 16.8% and 6.6%, respectively. Phylogenetic analysis of the partial rotavirus VP7 and VP4 coding genes revealed that all of these G9P [8] strains belonged to the lineage III and the P [8]-3 lineage, respectively, and shared the same genetic background (G9-P[8]-I1-R1-C1-M1-A1-N1-T1-E1-H1) as did most of previously detected G9P[8] strains and particularly the emerging G9P[8] strains from the 2004–2005 season in France. Conclusions: G9P[8] rotaviruses have become the predominant circulating genotype for the first time since their emergence a decade ago. In the absence of rotavirus immunization programmes in France, our data give an insight into the natural fluctuation of rotavirus genotypes in a non-vaccinated population and provide a base line for a better interpretation of data in European countries with routine rotavirus vaccination.